COMPONENTS AND DEVELOPMENT IN BIG DATA SYSTEM: A SURVEY - Sudhir Allam (International Journal of Innovations in Engineering Research and Technology, 2017)
This paper examines the principal components and develops the big data method. Through the expansion of distributed processing platforms, new Big Data research application items often have a variety of features. When people come into touch with Big Data systems early on, it is difficult for them to make choices [1]. The components designed for the big data framework based on specifications are presented in this paper. Conventional databases may not handle unstructured data and high amounts of real-time data sets. Various databases contribute to large data and it is difficult, utilizing conventional database methods, to archive, maintain, process, interpret, visualize, and derive valuable information from such data sets [2]. However, there are also technical aspects to the refining of massive heterogeneous Big Data trends. The components explored in this paper involve those in the data access layer, data collection layer, data analysis, and data processing layer of the big data system